Presentación - Esteban Arias-Méndez (Tecnología en Marcha)
IEEE Latin American Electron Devices Conference (LAEDC) 2023 welcome you to this fifth edition. LAEDC is the flagship conference for EDS in Region 9 and offers an enriching opportunity to learn about many of the fields related to Electron Devices and novel technologies. This special issue is focused on the short papers related to EDS topics presented at the conference.